2019
DOI: 10.3389/fpsyg.2019.02453
|View full text |Cite
|
Sign up to set email alerts
|

Trait Emotional Intelligence and Classroom Emotions: A Positive Psychology Investigation and Intervention Among Chinese EFL Learners

Abstract: The link between emotional intelligence (EI) and negative emotions, especially anxiety, has been investigated in different educational contexts including second/foreign language (L2) learning contexts. However, the link between EI and positive emotions remains underexplored, despite the growing interest of second language acquisition (SLA) researchers in positive emotions, motivated by the Positive Psychology (PP) movement. Grounded on PP theories, a correlational and experimental investigation was conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 103 publications
4
69
1
Order By: Relevance
“…This result makes sense as having positive attitudes towards a FL, combined with a strong motivation to master the language really well, provides a firm basis on which a more fleeting emotion such as FLE can emerge during specific activities in the classroom (Gardner, 1985). FLCA was negatively linked with FLE, as was found in previous research (Dewaele & MacIntyre, 2014Li, 2020;Li & Xu, 2019;Resnik & Dewaele, 2020), and with attitudes/ motivation. This fits with the pattern uncovered in MacIntyre et al (2019), where negative emotions were found to be negatively linked with positively oriented attitudes/motivation dimensions and where strong positive relationships emerged between positive emotions and positively oriented attitudes/motivation towards the FL.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This result makes sense as having positive attitudes towards a FL, combined with a strong motivation to master the language really well, provides a firm basis on which a more fleeting emotion such as FLE can emerge during specific activities in the classroom (Gardner, 1985). FLCA was negatively linked with FLE, as was found in previous research (Dewaele & MacIntyre, 2014Li, 2020;Li & Xu, 2019;Resnik & Dewaele, 2020), and with attitudes/ motivation. This fits with the pattern uncovered in MacIntyre et al (2019), where negative emotions were found to be negatively linked with positively oriented attitudes/motivation dimensions and where strong positive relationships emerged between positive emotions and positively oriented attitudes/motivation towards the FL.…”
Section: Discussionsupporting
confidence: 84%
“…There are probably a number of mediating factors that were not included in the current research design (cf. Li, 2020;Li & Xu, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent that a good memory for vocabulary is a prerequisite for mastery of English because "the heart of language comprehension and use is the lexicon" [68]. The current study shows that watching a laughter-provoking video clip after English vocabulary learning reduced associative memory for English words, suggesting that English teachers should be cautious in drawing on positive emotion intervention as teaching strategy [e.g., humor in L2 teaching in the study of [69][70][71] in classroom practices. Specifically, after the learning of English vocabulary, it may behove a learner to be emotionally neutral.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 83%
“…In fact, implementation of programs that target emotional intelligence, and especially the adaptability and interpersonal factors of it, should become a priority in schools to improve not only the learning processes of their students, but also their present and future well-being. Many studies have shown the effectiveness of EI school interventions in improving a student's EI, either when learning a second language [72] or in the regular school setting [73]. These interventions boost more positive classroom emotions and alleviate negative ones, facilitating the learning process of the students.…”
Section: Discussionmentioning
confidence: 99%